Targeting matrix metalloproteinase‐13 in bronchial epithelial repair. Issue 9 (31st July 2018) - Howell, Christopher; Smith, James R.; Shute, Janis K.
Abstract: Background: Viral infection of the bronchial epithelium disrupts the barrier properties of the epithelium in healthy individuals and those with lung disease. Repair of the bronchial epithelium is dependent of the formation of a provisional fibrin matrix and migration of epithelial cells to cover denuded areas, followed by proliferation and differentiation. Objective: The objective was to test the hypothesis that poly I:C, a model of viral infection, limits epithelial repair through the stimulated release of matrix metalloproteinase‐13 (MMP‐13). Methods: Confluent layers of cultured normal human primary bronchial epithelial cells (NHBE) and SV‐40 virus‐transformed 16HBE14o‐ bronchial epithelial cells were mechanically wounded, and video microscopy used to measure the rate of wound closure over 2 hours, in the absence and presence of poly I:C (1‐20 μg/mL). MMP‐13, tissue factor and endothelin release were measured by ELISA. The effect of inhibitors of MMP‐13 activity and expression and a nonspecific endothelin receptor antagonist, bosentan, on the rate of epithelial repair was investigated. Results: Poly I:C limited the rate of epithelial repair, and NHBE were significantly more sensitive to poly I:C effects than 16HBE14o‐ cells. NHBE, but not 16HBE14o‐, released MMP‐13 in response to poly I:C. Inhibitors of MMP‐13 activity (WAY 170523) and expression (dimethyl fumarate) significantly enhanced the rate of repair. Bosentan enhanced the rate of bronchial epithelial repair by a mechanism that was independent of MMP‐13. Conclusions and clinical relevance: Bronchial epithelial repair is limited by endothelin and by MMP‐13, a protease that degrades coagulation factors, such as fibrinogen, and matrix proteins essential for epithelial repair. Further studies with primary cells from patients are needed to confirm whether repurposing bosentan and inhibitors of MMP‐13 expression or activity, for inhalation may be a useful therapeutic strategy in diseases where repeated cycles of epithelial injury and repair occur, such as asthma and COPD.